Law and the importance of its formal dimension - Morales Luna, Félix Francisco (2023)
This article highlights the importance of the formal dimension of legal systems for the full realization of the purposes of Law in a society, in view of the changes they have undergone due to the process of their constitutionalization. Based on the systemic theory of life, which highlights the form and pattern of organization of living beings, and projecting it to social systems, Law is presented as an emergent property of social systems, defined from its forms, on which its effectiveness depends.From this theoretical framework, it also analyzes the change of paradigm in the theories of Law and suggests that the identity of legal positivism must be reconstructed around the formal dimension of legal systems to maintain its validity in current debates.Finally, a reflection on the moral commitment of the jurist to the forms and procedures of the legal system with which he works is included.